2013
DOI: 10.1038/hdy.2013.17
|View full text |Cite
|
Sign up to set email alerts
|

Use of multiple markers demonstrates a cryptic western refugium and postglacial colonisation routes of Atlantic salmon (Salmo salar L.) in northwest Europe

Abstract: Glacial and postglacial processes are known to be important determinants of contemporary population structuring for many species. In Europe, refugia in the Italian, Balkan and Iberian peninsulas are believed to be the main sources of species colonising northern Europe after the glacial retreat; however, there is increasing evidence of small, cryptic refugia existing north of these for many cold-tolerant species. This study examined the glacial history of Atlantic salmon in western Europe using two independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…; Finnegan et al . ). Evidence from mtDNA haplotypes alone suggests that the shallow‐ and deep‐pelagic clades diverged over 22 000 years ago, in correspondence with the last glacial maximum (LGM) .…”
Section: Discussionmentioning
confidence: 97%
“…; Finnegan et al . ). Evidence from mtDNA haplotypes alone suggests that the shallow‐ and deep‐pelagic clades diverged over 22 000 years ago, in correspondence with the last glacial maximum (LGM) .…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, this group of haplotypes could have arisen within an additional, unidentified refugium, where R. clavata persisted during the last glacial maxima. There is growing evidence from a number of marine species that many organisms survived in isolated populations much closer to the ice sheets than previously thought (Provan et al 2005;Hoarau et al 2007;Olsen et al 2010;Finnegan et al 2013). This has been suggested in previous studies of R. clavata to explain the diversity of haplotypes present in northern Europe (Chevolot et al 2006), putatively suggesting Hurd Deep (i.e.…”
Section: Control Region Analysismentioning
confidence: 93%
“…Mitochondrial and nuclear data both, independently, support this time frame. Interestingly, Finnegan et al (2013) reported that Atlantic salmon also colonized Ireland from two separate refugia after the LGM.…”
Section: Resultsmentioning
confidence: 99%
“…The origins of Ireland's fauna and flora is still a contentious issue in biogeography; its geographical position as an outlying island in western Europe presents many difficulties in terms of how and when freshwater species in particular colonized it. Only Finnegan et al (2013) thus far has attempted to date the origins of a fish species, the Atlantic salmon (Salmo salar), in Ireland. Clearly, a landlocked population can provide fascinating insights into the origin(s) of Irish freshwater fish, in terms of both timing and source populations.…”
Section: Introductionmentioning
confidence: 99%